Strategi Pemberitaan Media Online Tribun Ambon dalam Menarik Viewers melalui Media Sosial Youtube - Dian, Wa; Hakis, Hakis; Tuanany, Iftiya (Journal of Management, Education and Communication, 2024)
This study aimed to determine the dissemination strategy of Tribun Ambon news media to attract viewers and increase the number of viewers through YouTube and its graphic data as well. This research used a qualitative descriptive method with a phenomenological approach. Data collection instruments employed in this study were observation, interviews, and documentation. The results of the study showed that Tribun Ambon news media implemented various strategies to attract viewers through online media, namely, (1) viral news content, (2) breaking news, and (3) the use of keywords or tags on Tribun Ambon's YouTube account. Through this strategy, there has been a continuous increase in the number of viewers of Tribun Ambon online media every month for the last three years (2022-2024). Tribun Ambon viewers increased by 8,390 visitors in January 2022 and 2024 have reached 344,000 visitors. Based on this data, viewers' interest in the videos presented by Tribun Ambon has experienced greater development